2009
DOI: 10.1007/s00249-009-0484-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel effects of methyl viologen on photosystem II function in spinach leaves

Abstract: Methyl viologen (MV) is a well-known electron mediator that works on the acceptor side of photosystem I. We investigated the little-known, MV-induced inhibition of linear electron flow through photosystem II (PS II) in spinach-leaf discs. Even a low [MV] decreased the (1) average, light-adapted photochemical efficiency of PS II traps, (2) oxidation state of the primary quinone acceptor Q(A) in PS II during illumination, (3) photochemical efficiency of light-adapted open PS II traps, (4) fraction of absorbed li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Fan et al . found that low MV concentrations decreased the chlorophyll‐ a fluorescence yield corresponding to dark‐adapted reaction centers ( F 0 ) and closed reaction centers ( F m ) and also diminished the light‐adapted photochemical efficiency of PSII. Our results with MV on F. benjamina , H. helix and S. wallisi agreed with the previous study published by Fan et al .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Fan et al . found that low MV concentrations decreased the chlorophyll‐ a fluorescence yield corresponding to dark‐adapted reaction centers ( F 0 ) and closed reaction centers ( F m ) and also diminished the light‐adapted photochemical efficiency of PSII. Our results with MV on F. benjamina , H. helix and S. wallisi agreed with the previous study published by Fan et al .…”
Section: Discussionmentioning
confidence: 98%
“…Several authors have already studied changes in the yield of chlorophyll fluorescence in the presence of herbicides . Conrad et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1; Bendall and Manasse, 1995;Joliot and Joliot, 2002). By reacting with any electrons coming from PSI, MV inhibits CEF and diverts LEF (Yu et al, 1993;Herbert et al, 1995) toward ROS production (Jia et al, 2008;Fan et al, 2009). In the presence of MV, the ROS production in a cell is thus mostly dependent upon the absolute number of electrons passing through PSI complexes per time unit, which results from two parameters that are both strongly influenced by growth irradiance: the electron transport rate at PSI complexes and the number of PSI complexes per cell.…”
Section: Identification Of Functional Groups Responding To Oxidative mentioning
confidence: 99%
“…Recent studies (e.g. Fan et al 2009) report negative effects on PS II, effective quantum yield in particular. In algae, however, MV effects on PS II / PS I are much less studied.…”
Section: Introductionmentioning
confidence: 99%